Influenza Vaccination Rates Among Patients With a History of Cancer: Analysis of the National Health Interview Survey. (20th April 2021) - Chang, Andres; Ellingson, Mallory K; Flowers, Christopher R; Bednarczyk, Robert A
Abstract: Background: Annual influenza vaccination is recommended for all patients with cancer, but vaccine uptake data by cancer type and time since diagnosis are limited. We sought to estimate vaccination rates across different cancer types in the United States and determine whether rates vary over time since diagnosis. Methods: Vaccination rates in individuals with solid tumor and hematological malignancies were estimated using data from 59 917 individuals obtained by the 2016 and 2017 National Health Interview Survey conducted by the Centers for Disease Control and Prevention. Results: An average of 64% of the 5053 individuals with self-reported cancer received the influenza vaccine. Vaccination rates in men and women with solid tumors (66.6% and 60.3%, respectively) and hematological malignancies (58.1% and 59.2%, respectively) were significantly higher compared to those without cancer (38.9% and 46.8%, respectively). Lower rates were seen in uninsured patients, those younger than 45 years of age, and in African Americans with hematological malignancies but not with solid tumors. Vaccine uptake was similar regardless of time since cancer diagnosis. Conclusions: Influenza vaccination rates are higher in men and women with cancer but remain suboptimal, highlighting the need for additional measures to improve vaccine compliance and prevent complications from influenza across all cancer types.